2021
DOI: 10.34190/ejel.19.6.2172
|View full text |Cite
|
Sign up to set email alerts
|

Learning Foreign Languages in a Digital Environment: Learners’ Perception of the Sudden Transition to e-Learning During COVID-19 Lockdown

Abstract: The research is devoted to the study of the forced and accelerated transition of education to an online environment on the example of learning a foreign language. Despite a large number of studies on e-learning, this study is one of the newest investigating recent education transformation trends. The ultimate goal of this paper was to study changes in students’ assessments of the e-learning process, participation in online-based education, and academic success during the transition to virtual training. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, some researchers [9][10][11] reported similar research results, demonstrating that online educational methods were effective in response to the development of the COVID-19 epidemic. Moreover, Ibrahim et al [12] proposed a case study of online foreign language learning from the perspective of Russian students. They found that these characteristics of usefulness, comfort, and acceptability were important factors for students in the digital learning environment.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…Interestingly, some researchers [9][10][11] reported similar research results, demonstrating that online educational methods were effective in response to the development of the COVID-19 epidemic. Moreover, Ibrahim et al [12] proposed a case study of online foreign language learning from the perspective of Russian students. They found that these characteristics of usefulness, comfort, and acceptability were important factors for students in the digital learning environment.…”
Section: Introduction 1research Backgroundmentioning
confidence: 99%
“…E-learning was more effective than conventional learning (Aboagye et al, 2021;Mahrlamova & Chabanovych, 2021). Practically, It could apply for the further transformation of educational programs and additional preparation of educators with the aim of facilitating learning transition to an online mode (Code et al, 2020;Ibrahim et al, 2021). On the other hand, the impact of the teaching and learning process during COVID-19 had the ability to made it easier to improve communication (Alawamleh et al, 2020;Kadir et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the research conducted by Ibrahim et al among 600 students from five private specialised educational institutions in Moscow (the Russian Federation) in 2021 revealed that during this forced language learning instruction the perception of online English learning as far as the three areas researched, i.e. the usefulness, comfort and acceptability of e-learning, decreased significantly in all the aspects 12 . Pawlak et al 13 , on the other hand, studied which class mode (online versus physical classes) was more boring for teachers and learners.…”
Section: Introductionmentioning
confidence: 99%